UJI AKURASI PEMBACAAN MOTIWALI TERHADAP JARAK TRANSDUSER DENGAN DENSITAS PERMUKAAN MEDIUM YANG BERBEDA - Jefry Bemba; Nurhalis Wahidin (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
MOTIWALI is a tidal measuring instrument that uses sound wave. This study aims to identify the limiting factor and accuracy of MOTIWALI to measuring transducer with the surface medium. The sound propagation was affected by temperature and medium density condition as the reflected plane. Reading test were conducted with three different medium density groups (salt water, fresh water, estuary) as well as transducer high treatment (5 treatments). Suitability of distance reading by the tranducer and recording interval was analyzed using ANOVA dan principle component analysis (PCA). The result showed that instrument did not give the difference of distance reading to the surface of medium, but different densities to data recording intervals with the time set in confiq.sys. MOTIWALI effective work at a distance of 150cm from the medium surface and fixing the recording time was added for 1 minute.